Temporal dynamics of botrytis bunch rot (Botrytis cinerea) in Cabernet Franc grapevine as a function of increased bud load - Wurz, Douglas André (2021)
The increase in the vegetative canopy and the thickening of bunches in the plant caused by the higher number of plant-1 buds can create a favorable microclimate for the occurrence of Botrytis bunch rot. This study aimed to evaluate the effect of increasing plant-1 bud load on epidemiological variables of Botrytis bunch rot (Botrytis cinerea) in the Cabernet Franc vine cultivated in an altitude region of Santa Catarina State. The present work was carried out during the 2016/2017 harvest, in a commercial vineyard, located in the municipality of São Joaquim. The treatments consisted of four different pruning levels: 15 buds plant-1, 30 buds plant-1, 50 buds plant-1, 75 buds plant-1. It was evaluated: maximum incidence, maximum severity, AACPID, AACPSD, TAMID, TAMSD and IAS. It was observed an effect of plant-1 bud load on the epidemiological variables of Botrytis bunch rot in the Cabernet Franc grapevine bunches. The increase in bud load resulted in an increase in the incidence and severity of the disease, AACPID and AACPSD, the highest being observed in plants submitted to winter pruning with a bud load greater than 50 buds plant-1. The adoption of a high number of plant-1 buds must be accompanied by integrated disease management practices that aim to reduce the effects caused by the occurrence of Botrytis bunch rot.